Gestational diabetes mellitus in previous pregnancy associated with the risk of large for gestational age and macrosomia in the second pregnancy - Wang, Ying; Yang, Juan; Liu, Yuzhen; Yang, Ao; Deng, Yuqing; Xu, Chang; Zhong, Shilin (Frontiers in Endocrinology, 2025)
BackgroundSince the implementation of China’s new birth policy, the incidence of large for gestational age (LGA) and macrosomia associated with gestational diabetes mellitus (GDM) has increased. It remains unclear whether a history of GDM in a previous pregnancy raises the risk of LGA or macrosomia in Chinese women planning two or more pregnancies.AimTo analyze the association between previous GDM and the risk of LGA and macrosomia in second pregnancy.MethodA retrospective study was conducted on a cohort of 3,131 women who had experienced two consecutive singleton births. The incidences of LGA and macrosomia in the second pregnancy were compared between women with and without previous GDM. The relationship between previous GDM and the occurrence of LGA and macrosomia was analyzed using multivariate logistic regression and stratified analysis.ResultsThe incidence of LGA and macrosomia during the second pregnancy was significantly higher in women with previous GDM (22.67% and 10.25%, respectively) compared to those without prior GDM (15.34% and 5.06%, respectively) (P < 0.05). After adjusting for potential confounders, previous GDM was significantly associated with LGA (aOR: 1.511, 95% CI: 1.066-2.143) and macrosomia (aOR: 1.854, 95% CI: 1.118-3.076) in the second pregnancy. Stratified analysis revealed that these associations were present only in women without previous LGA, those with GDM, appropriate gestational weight gain (AGWG), non-advanced maternal age, and male newborns during the second pregnancy (P < 0.05). Compared to excessive GWG (EGWG), AGWG correlated with lower risks for LGA and macrosomia during the second pregnancy in women without prior GDM, an association not observed in those with previous GDM. Among women without previous GDM, if the pre-pregnancy BMI is normal, the risk of LGA and macrosomia is significant lower in AGWG compared with EGWG (P< 0.001), while this difference was no significant among women with prior GDM (P>0.05).ConclusionPrevious GDM is strongly linked to LGA and macrosomia in subsequent pregnancies. However, this relationship is influenced by GWG, prior LGA history, fetal sex, and maternal age. Managing weight alone may not sufficiently reduce the risk of LGA or macrosomia for women with a history of GDM.